Designing Hierarchical ZSM-5 Materials for Improved Production of LPG Olefins in the Catalytic Cracking of Triglycerides. (2nd May 2019) - Vu, Xuan Hoan; Armbruster, Udo
Abstract : LPG olefins (propene and butenes) are key building blocks in the petrochemical industry whose demand has been expanding steadily in recent years. The use of FCC (fluid catalytic cracking) units for conversion of triglycerides is a promising option for the future to boost production of LPG olefins. However, a need for innovative cracking catalysts is rising due to the different nature between petroleum and biomass-derived feedstocks. In this study, series of hierarchical ZSM-5 materials, namely, mesoporous ZSM-5, nanosized ZSM-5, and composite ZSM-5 were prepared, aiming to enhance the production of LPG olefins along with transportation fuels. Mesoporous ZSM-5 materials were synthesized by the postsynthetic modifications involving base treatment and subsequent acid washing, whereas nanosized ZSM-5 and composite ZSM-5 were synthesized by the direct-synthetic routes for a comparative purpose. The obtained materials were characterized by XRD, FTIR, N2 sorption, TEM, AAS, ICP-AES, and NH3 -TPD, and their catalytic performance was assessed in the cracking of triolein as a representative of triglycerides under FCC conditions. It was found that the subsequent strong acid washing step of alkaline treated ZSM-5 for removal of aluminum debris and external acid sites is needed to improve the catalytic performance. The resulting mesoporous ZSM-5 material shows higher yields of the desired products, i.e., gasoline and LPG olefins than its parent, commercial ZSM-5 at the almost complete conversion (ca. 90 wt.%). The selectivity toward LPG olefins is also enhanced over all the hierarchical ZSM-5 materials, particularly high for composite ZSM-5 (ca. 94 wt.%). The improved diffusion and lowered acidity of the hierarchical ZSM-5 materials might be responsible for their superior catalytic performance.